Determinants of Informal Labor Income: Does Demographic Matters? - Dinar Melani Hutajulu; Rr. Retno Sugiharti; Jihad Lukis Panjawa; Jalu Aji Prakoso; Lorentino Togar Laut (Jurnal Ekonomi dan Studi Pembangunan, 2021)
In informal sector, labor is unnecessary to have a higher degree and special skill. So that, working in informal sector is one of the solutions for labor with low skill to gain an income and move out from poverty. This research aims to analyse determinant factors of labor income in informal sector, focused on demographic and social economics variables. By using SAKERNAS data from Indonesian Statistics, this research is adopted Mincer Wage Equation and conducted by Ordinary Least Square Method. The result shows that Mincer Equation still a robust model for modelling wage factor. Labor with more educational backgrounds come up with higher income since the education will refine the workability and capability to improve productivity. In the other hand, labor in informal sector who live in the village earn more income than those who work in the city area. This conclude that by right policy, informal sector can develop higher income as high as formal sector.